ITSENKO-CUSHING SYNDROME: A SET OF SYMPTOMS THAT OCCUR ON THE BACKGROUND OF HYPERCORTISOLISM (Proceedings of International Educators Conference, 2024)
Cushing syndrome is a hormonal disorder caused by prolonged exposure to inappropriately high levels of plasma glucocorticoid (also referred to as cortisol) hormones. Glucocorticoid hormones maintain glucose regulation, suppress the immune response and are released as part of the body's response to stress. The production of cortisol from within the cortex of the adrenal glands is regulated by a small gland just below the brain called the pituitary gland.